2016
DOI: 10.1016/j.bpj.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Membrane Potential of Simple Dual-Membrane Systems as Models for Gap-Junction Channels

Abstract: The conductance of ion channels can be modulated by a transmembrane potential difference, due to alterations on ion-mobility and also by changes in the pore structure. Despite the vast knowledge regarding the influence of voltage on transport properties of ion channels, little attention has been paid to describe, with atomic detail, the modulation of ionic transport in gap-junction channels (GJCs). Hence, molecular dynamics simulations were performed to explore the conductance of simple dual-membrane systems t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…A lack of structural details of Cx isoforms is a major hurdle for accurate modeling at this stage. Simplified models implementing pore wall charges in in silico studies with Cx26 channels have been reported (Escalona et al, 2016). Such simplified application of pore electrostatics can be envisioned to study the role of different combinations of charges and in-pore charge-locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lack of structural details of Cx isoforms is a major hurdle for accurate modeling at this stage. Simplified models implementing pore wall charges in in silico studies with Cx26 channels have been reported (Escalona et al, 2016). Such simplified application of pore electrostatics can be envisioned to study the role of different combinations of charges and in-pore charge-locations.…”
Section: Discussionmentioning
confidence: 99%
“…Structural details are a requisite for using existing computational approaches for studying membrane channels like ion channels (Allen et al, 1999; Corry et al, 2001; Chung et al, 2002; Vora et al, 2008) and porins (Schirmer and Phale, 1999; Im and Roux, 2002; Lee et al, 2011). Molecular modeling of Cx26 hemichannels (Kwon et al, 2011; Zonta et al, 2014) and gap junctions (Bennett et al, 2016; Escalona et al, 2016) was performed for studying their structure/function relations. Limitations and difficulties in deriving such structures pose a barrier to studying the structure and permeability of the whole range of gap junction channel types.…”
Section: Introductionmentioning
confidence: 99%
“…GJCs are formed by the extracellular docking of two HCs, (Figure 2.A), where each HC is formed by six CXs monomers ( Figure 2.B). In this example, we studied a 20ns all-atom MD simulation of a complete GJC formed by the human CX26 [13]. This molecular system contains twelve identical CX monomers in total, each one comprising 226 AAs.…”
Section: Md2: An Example Of a Conformational Changementioning
confidence: 99%
“…GJs are composed of two adjacent hemichannels which anchor to each other, forming a hydrophilic channel ( 6 ) for intercellular communication via small molecules, such as inorganic ions (calcium and potassium), amino acids and glucose ( 7 , 8 ). GJs are dynamic structures, and a variety of factors are involved in regulating their opening and closing, such as intracellular pH, calcium ion (Ca 2+ ) concentration, and membrane potential ( 9 ). GJs have functions in cell metabolism and differentiation, transmission of nerve impulses and conduction of information, coordination of consistency between cellular activity, material transport, and electrical excitation conduction ( 10 ).…”
Section: Introductionmentioning
confidence: 99%